Biochemical conversion of waste paper slurries into bioethanol - Tolulope Eunice Kolajo; Joy Elohor Onovae (Scientific African, 2023)
Waste papers, which are a major constituent of municipal wastes, can be repurposed into the production of bioethanol, a renewable and ecofriendly fuel. Many studies have produced ethanol from print-grade papers, but literature on conversion of waste cartons is sparce. In this study, waste corrugated cartons and print-grade papers were reduced into slurries and were subjected to physical and chemical tests to determine their suitability for biosynthesis. Cellulose fibers in the slurries were directly hydrolyzed into glucose without prior pretreatment by dilute hydrochloric acid, and fermented into ethanol using Saccaromyces cerevisae. Density, flammability, color, odor, non-volatile residue and other qualitative tests were conducted on the ethanol produced. Glucose yield and the extraction efficiency in cellulose hydrolysis were significantly higher for waste cartons than print paper slurries. Qualitative tests reveal that the ethanol produced from both slurries has physical and chemical characteristics that are comparable to laboratory grade ethanol, contains no toxic impurities, and is suitable for use as a biofuel.